2005
DOI: 10.1128/jb.187.11.3800-3806.2005
|View full text |Cite
|
Sign up to set email alerts
|

The ExsA Protein of Bacillus cereus Is Required for Assembly of Coat and Exosporium onto the Spore Surface

Abstract: The outermost layer of spores of the Bacillus cereus family is a loose structure known as the exosporium. Spores of a library of Tn917-LTV1 transposon insertion mutants of B. cereus ATCC 10876 were partitioned into hexadecane; a less hydrophobic mutant that was isolated contained an insertion in the exsA promoter region. ExsA is the equivalent of SafA (YrbA) of Bacillus subtilis, which is also implicated in spore coat assembly; the gene organizations around both are identical, and both proteins contain a very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
68
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 40 publications
3
68
0
Order By: Relevance
“…Although it is named as a putative exosporium protein and involved in proper exosporium assembly, ExsA is not likely a true exosporium component. It possesses a conserved Nterminal cortex binding domain which suggests that it resides in the inner coat layer of the spore (41). ExsA displays sequence similarity to the B. subtilis SafA spore protein that functions in spore coat assembly.…”
Section: Exsa (Bas4324)mentioning
confidence: 99%
See 2 more Smart Citations
“…Although it is named as a putative exosporium protein and involved in proper exosporium assembly, ExsA is not likely a true exosporium component. It possesses a conserved Nterminal cortex binding domain which suggests that it resides in the inner coat layer of the spore (41). ExsA displays sequence similarity to the B. subtilis SafA spore protein that functions in spore coat assembly.…”
Section: Exsa (Bas4324)mentioning
confidence: 99%
“…These have been identified through the isolation of mutants that fail to stably attach the exosporium and from which, as a consequence, the exosporium is released as sheets separate from the mature spores upon lysis of the mother cells. Proteins implicated in exosporium attachment include the spore coat protein CotE and the exosporium-or interspace-localized proteins CotY, ExsA, ExsB, ExsY, and ExsM (1,(41)(42)(43)(44)(45). Whether these proteins participate directly in exosporium attachment or indirectly, through proper positioning of proteins actually involved in the attachment, has not been established.…”
Section: The Exosporium Layer Of Bacterial Sporesmentioning
confidence: 99%
See 1 more Smart Citation
“…In some species such as Bacillus anthracis and Bacillus cereus, the outermost layers are formed by the exosporium, which is composed of at least 21 protein species forming a paracrystalline basal layer and a hair-like nap composed mainly of collagen-like proteins, such as BclA and BclB (6,9,10). The components of the spore coat and exosporium layers are synthesized in the mother cell and subsequently assembled on the developing forespore (6).…”
mentioning
confidence: 99%
“…However, bioinformatic analysis has shown that these proteins are absent in other species that have an exosporium layer (i.e., C. difficile) (6). Below the exosporium is the spore coat, where several morphogenetic factors essential for the proper assembly of the coat of Bacillus subtilis, B. anthracis, and B. cereus spores include ExsA (SafA orthologue), CotE, ExsB (CotG analogue), ExsY (CotZ orthologue), CotB, CotY, and ExsK (a cysteine-rich protein related to CotX) (10,11,14). However, the ultrastructure of C. difficile 630's spore exosporium layer is significantly different from that of B. anthracis spores (7,8,17) and bioinformatic and proteomic analyses (6,18) indicate that the exosporium proteins of B. anthracis and B. cereus are absent in C. difficile, suggesting that the exosporium of C. difficile spores is made of proteins that are highly divergent.…”
mentioning
confidence: 99%